EFFECT OF L-CARNITINE SUPPLEMENT TO THE SPERMS IN THE MATURATION MEDIA - Al-Mustafa E. Kadum, Noor; A. Hatif, Saad; N. Al- Okaily, Baraa (International Journal of Psychosocial Rehabilitation, 2021)
and the study aimed to explore the role of L-Carnitine supplementation on epididymis spermatozoa of bull, in maturation media. Cattle were a study model, samples of the reproductive systems from the slaughter Al-Shoáalla abattoir) were chosen, many samples of slaughtered bulls’ testes. All samples were transferred to the laboratory in a thermos containing sterilized phosphate-buffered saline at 33-35°. Aspiration and slicing methods were used to collection the epididymal fluid, and then the evaluations and matured. The study was showing adding a different consternation of L-carnitine leads to significant increase in pH at (p<0.05). Highest increment of parameter after 3 hours of incubation was recorded at concentration 60 µm with mean value were (7.78±0.05 µm) and (6.90±0.04 µm) respectively. The less significant (p<0.05) increasing was found in concentration 120 µm. The result was showing increase in the sperm maturation (70%) at concentration (60 µm) of L-carnitine compart with non-treated (control) group after 3 hours of the experiment with significant difference (37.80±3.90 µm) and (79.40±3.07 µm) respectively at (p<0.0001).The result was appeared a significant increase in peroxy-nitrite concentration (12.00±1.22 µm) of treatment with L- carnitine comparing with (59.80±2.28 µm) of control group at (0.001) after 3.hr with contraction of L- carnitine 60 µm. The results were showed a significant decrease in glutathione concentration GSH of L-carnitine (12.00±1.22 µm) comparative with control (59.80±2.28 µm) on spermatozoa after 3hr incubation in the TCM media. The study was showing adding a different consternation of L-carnitine leads to significant increase in pH at (p<0.05). Highest increment of parameter after 3 hours of incubation was recorded at concentration 60 µm of L-carnitine with mean value (9.6±0.03µm) and (6.72±0.03µm) respectively at (p<0.01). The study was showed increasing in pH value in concentration 120 µm of L-carnitine. The study was showed significant increases in the maturation percent of oocytes after 24hr incubation in the TCM media,